Biocidal activity of ROMP- polymer coatings containing quaternary phosphonium groups - Demir, Ceren; Suer, N. Ceren; Yapaoz, Melda Altikatoglu; Kebir, Nasreddine; Okullu, Sinem O.; Kocagoz, Tanil; Eren, Tarik (ELSEVIER SCIENCE SA, 2019)
Bacterial surface contamination is considered as one of the main causes of secondary infection. Herein, cationic polymers containing alkyl or aromatic quaternary phosphonium groups were synthesized via ring opening metathesis polymerization (ROMP) and successfully deposited onto a glass surface via a spin coating or dip coating process in an effort towards preventing biofilm formation. The polymer bearing phenyl units with a molecular weight of 3000 g mol(-1)(G_Phenyl_3k) exhibited the highest bactericidal efficiency against an E. coli contaminated solid surface with a bacteria killing efficiency of 80%. However, increasing the molecular weight of the polymer (10,000 g mol(-1)) caused a dramatic decrease in the bactericidal activity (10%). Polymers bearing alkyl group also exhibited lower biocidal activity on the solid surface, which was similar to that observed in solution. The bactericidal effect of the active surfaces against E. coli were confirmed using a live and dead fluorescent assay. The accessible surface positive charge density of the as-prepared polymer-coated surfaces was calculated using a staining with fluorescein sodium salt and varied from 3.5 x 10(14) to 1.9 x 10(15) charge cm(-2). The dispersive and the polar components of the surface energy as well as polarity of the coated surfaces were also evaluated using contact angle measurements. The surface polarity (%), cationic charge density and threshold concentration were found to influence the biocidal activity observed on the polymer-coated solid surfaces.
Keywords: Biocidal surface; ROMP; Phosphonium; Structure-property relationship; ANTIBACTERIAL POLYMERS; CATIONIC BIOCIDES; CHAIN-LENGTH; SURFACES; BACTERIA; INFECTIONS; COPOLYMERS; AMMONIUM; SALTS; Chemistry; Materials Science